PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN,PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH,SISTEM INFORMASI AKUNTANSI KEUANGAN DAERAH, DAN PRINSIP PENGELOLAAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN BADUNG - I Gusti Ayu Ratih Dwi Artatik; Ni Wayan Alit Erlina Wati; Putu Nuniek Hutnaleontina (UNHI Press, 2021)
The Government Regulation regarding Government Accounting Standards states that financial statements are structured reports of financial position and transactions conducted by a reporting entity. The quality of financial reports can be said to be of quality if they can meet the qualitative characteristics of financial statements contained in Government Regulation Number 71 of 2010 concerning Government Accounting Standards, namely: Relevant, Reliable, Comparable, Understandable. Many factors affect the quality of financial reports, this research uses internal control system variables, understanding of government accounting standards, regional financial accounting information systems, and regional financial management. The main objective of this research is to find out whether there is an influence from the internal control system, understanding of government accounting standards, regional financial accounting information systems, and regional financial management on the quality of financial reports at 38 OPDs of Badung Regency. The number of samples taken was 114 people, with purposive sampling technique. Data collection was carried out using a questionnaire. The data analysis technique used is multiple linear regression. The results showed that the application of the internal control system, understanding of government accounting standards, regional financial accounting information systems, and financial management principles had a positive effect on the quality of financial reports.